Cysteine Modifications in the Pathogenesis of ALS - Valle, Cristiana; Carrì, Maria Teresa (Frontiers in Molecular Neuroscience, 2017)
Several proteins are found misfolded and aggregated in sporadic and genetic forms of Amyotrophic Lateral Sclerosis (ALS). These include SOD1, TDP-43, FUS/TLS, p62, VCP, Ubiquilin-2 and dipeptide repeats produced by unconventional RAN-translation of the GGGGCC expansion in C9ORF72. Up to date, functional studies have not yet revealed a common mechanism for the formation of such diverse protein inclusions. Consolidated studies have demonstrated a fundamental role of cysteine residues in the aggregation process of SOD1 and TDP43, but disturbance of protein thiols homeostatic factors such as Protein Disulfide Isomerases, glutathione, cysteine oxidation or palmitoylation might contribute to a general aberration of cysteine residues proteostasis in ALS. In this paper we review the evidence that cysteine modifications may have a central role in many, if not all, forms of this disease.